Exploring Innovative Avenues for Muslim Students in Contemporary Society and Technology - Wahab Taiwo Bakare (Penerbit Hellow Pustaka, 2025)
Innovation is the practical process of moving an idea from concept to reality, and this idea can result in the introduction of new goods or services or improvement in offering goods or services. Scholars like Drucker (2002), Roger (2003) and Baregheh, et al (2009) have worked assiduously with different topics on innovation. The main intent of this work is to project some innovative works which Muslim students can do that can make them a better person in the society. This paper will explain to Muslim students on how to surmount the problem of scarcity by learning works, and by the time they finish the learning, they will be able to put it into practice, and by God's grace, it will yield them a profit. The paper will explain in detail on the reason why Muslim students should adventure on the innovative skills. It will explain and give clue on some areas in which Muslims students can explore their innovative skills in today’s society and technology. These areas of innovation could be in different fields like health, science and technology, creative arts etc. To make this work well understood, we went to collect data from different informants/innovators, and we interviewed them. We learned different ways of becoming a great innovator, and these ways shall be narrated in this paper. Theory of Innovation will be used to analyze our thoughts.